Riboswitches as targets and tools - Burke, Donald H. (Methods in enzymology, 2015)
This new volume of Methods in Enzymology continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume covers research methods in riboswitches as targets and tools and contains sections on such topics as constructing and optimizing artificial riboswitches, live cell imaging and intracellular sensors with artificial riboswitches, conditional control of gene expression with artificial riboswitches, using artificial riboswitches for protein evolution and pathway optimization, and anti-riboswitch drug screens. Continues the legacy of this premier se.